Individual, Occupational and Biomechanical Factors That Affect Slip and Fall Risk from Fixed Ladders - (:unkn) unknown (My University, 2015)
Injuries from ladder falls are prevalent and severe. Previous research has examined certain elements of ladder falls such as the ladder base slipping, but few studies have examined the factors that contribute to climbers falling from the ladder, particularly for permanent/fixed ladders. In addition, the biomechanical response to a ladder slip/misstep during ladder climbing and the factors that affect a fall from a ladder are not well understood. This thesis is a two part study that simulated ladder slips and missteps in order to find factors 1) associated with ladder slip risk and 2) that decrease fall severity from a ladder. Specifically, 32 participants were recruited for study 1 to investigate restricted toe clearance, hand positioning, age, climbing direction and climbing biomechanics with slip risk. Thirty-five participants were recruited for study 2 to investigate the impacts of gender, climbing direction, gloves, and hand and foot responses on fall severity. Study 1 found restricted toe clearance, younger ladder climbers, and climbing biomechanics with greater variation to be associated with an increased slip risk. Study 2 found that males, ascending climbs, post-perturbation hand placements that extended the arm, and foot responses that hit the top of a ladder rung were associated with decreased fall severity.
Keywords: Aging; Climbing Biomechanics; Fall Response; Gender; Hand Friction; Ladder Falls